Pervivencia de la narrativa picaresca en lengua alemana, inglesa y española - Iztueta Goizueta, Garbiñe (Vitor, 2003)
Picaresque narrative has transcended chronological and spatial limits, according to a series of critical studies. Even literary authors themselves, such as Günter Grass and Thomas Mann, have affirmed that they have written Die Blechtrommel and Bekenntnisse des Hochstaplers Felix Krull respectively according to the picaresque model. One of the aims of this work is to justify the persistence of a type of novel in the XX. century, when it originally arose in the cultural, social, political and literary context of the XVI. and XVII. century Spain. In order to achieve a historical, theoretical and critical study of the picaresque narrative, the first step of this work has been to set the typology of a picaresque novel. Taking three canonical Spanish picaresque novels (La vida de Lazarillo de Tormes, Guzmán de Alfarache and La vida del buscón) as a basis, with references to Simplicius Simplicissimus and The Fortunes and Misfortunes of the Famous Moll Flanders, four relevant features are to be considered axial for the picaresque narrative. First of all, it is in the picaresque novel where the narrative form adopted from the autobiography is for the first time used for fictional, secular and marginal actions. Second, the episodic structure shows recurrent episodes, such as marginal familiar inheritance, orphanhood, initiation, etc. The picaro is the third axial element of this narrative: product of a social and moral conflict, transgressor and trying very hard to progress in life, he